Unesco’s Draft of the Recommendation on the Ethics of Neurotechnology: Toward a Legal Framework for the Protection of Neuro-Rights and the Processing of Neuro-Data (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
This essay begins with an analysis of the Unesco’s draft of the Recommendation on the Ethics of Neurotechnology proposed, with the aim of examining the initial regulatory measures and judicial decisions concerning the so-called “neurorights”. In light of the ongoing doctrinal debate and the current legal framework on personal data protection, the essay further seeks to explore how these factors may influence the future regulation of the so-called “neurodata”.
Keywords: fundamental rights; neurorights; privacy; regulation; risks; opportunities